Question design in veterinary consultations: question forms and client responses in accomplishing problem presentation in a Malaysian context - Hussein Jamal, Noorjan; Chan, Mei Yuit; Rafik-Galea, Shameem; Yap, Ngee Thai; Lee, Geok Imm; Megat Abd Rani, Puteri Azaziah (Masaryk University Press, 2022)
Question design by medical practitioners has been shown to have important consequences on how patients present their problems in clinical consultations. Linguistic structure of questions as part of question design implements different communicative and pragmatic functions, and hence, affects patients’ response in different ways. This study examined types of questions asked by veterinarians in the problem presentation phase of the clinical consultation in relation to their linguistic forms and functions. Veterinary illness consultations were video-recorded and veterinarians’ question types, their linguistic forms and clients’ response in the interaction were identified and examined. The results show that the general inquiry question implemented using the open-ended wh-question structure and the closed-ended declarative interrogative are the preferred forms used by veterinarians to solicit patients’ presenting problems from clients. Also, alignment of the linguistic form of questions with their pragmatic functions and the discourse goal of problem presentation affects clients’ ascription of veterinarians’ actions. The findings from the study can inform veterinarian communication training for more effective veterinarian-client communication to accomplish problem presentation in clinical consultations.